Simulating the role of transportation infrastructure for community disaster recovery. Issue 3 (14th September 2022) - Blagojević, Nikola; Didier, Max; Stojadinović, Božidar
Abstract : Functional recovery of transportation infrastructure after a disaster is essential for community disaster resilience, as the recovery of damaged community components depends on their accessibility for repair. This paper presents a community disaster recovery simulation that accounts for community components' accessibility for repair using a demand–supply framework. The considered components of a community are viewed as suppliers and/or users of various resources and services essential for community functionality, reflected in components' supply and demand properties. Whenever the demand of a component is not met, that component ceases to operate, simulating interdependency effects. Similarly, recovery demand is attributed to damaged components, representing the amounts of resources and services (e.g. workers, machinery and transportation services) that these components need to recover. The proposed framework is illustrated on a virtual community with 3600 inhabitants supported by several interdependent infrastructure systems. The results show that the transportation network damage slows down the recovery of the virtual community by preventing access to damaged components and reducing the ability of the community to mobilise available repair resources. Furthermore, the effect of such prolonged transportation system recovery on the damage-free infrastructure systems whose functionality was decreased due to their dependency on the affected infrastructure systems, is quantified.